2017
DOI: 10.1186/s12978-017-0341-2
|View full text |Cite
|
Sign up to set email alerts
|

Male reproductive health challenges: appraisal of wives coping strategies

Abstract: BackgroundSystematic studies on the association between men’s sexual dysfunction (low sexual desire, ejaculation disorders, erectile dysfunctions, genital ulcers, testicular disorders, prostate cancer or sexually transmitted infections) and marital conflict are emerging. However, the coping strategies adopted by wives in such circumstances are not commonly reported in the literature. Male sexual functioning is vital to the marital relationship, lack of it can result in intolerable cohabitation or relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…The field notes and transcripts were read severally to enhance the researchers' understanding of the data. Recurring themes and answers were categorized through the adoption of the "scissors and paste" approach adopted by scholars such as Mitchell et al (2011) and Amoo et al (2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The field notes and transcripts were read severally to enhance the researchers' understanding of the data. Recurring themes and answers were categorized through the adoption of the "scissors and paste" approach adopted by scholars such as Mitchell et al (2011) and Amoo et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…Concepts were coded and subsequently structured into groups for each transcription and thereafter combined together. Themes were then developed by adding more concepts, combined or split (Amoo et al 2017(Amoo et al , 2018. Responses that proved difficult to be directly grouped into the themes were regrouped subsequent to the discussions among the reviewers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from the same study showed that one of the psychological causes of sexual dysfunction is relationship or marital problems (35) . Emmanuel et al (36) reported that male sexual performance ability is vital in the marital relationship so that the lack of it can lead to a failure in the relationships. Basically, socio-cultural and interpersonal factors play an important role in developing sexual concern, which can lead to sexual difficulty and sexual dysfunction (32) .…”
Section: Wife Marital Intimacymentioning
confidence: 99%
“…Erectile dysfunction is estimated to affect 152 million in the world (13). The prevalence of erectile dysfunction in the general population of America is 52% where the problem ranges from 35-75% among men with diabetes and it occurs at an earlier age (14).In Africa 12 million men are estimated to be affected by ED; as some reports show that in Nigerian in particular, more than three out of every 10 men have reported ED or another sexual problems (2,6,15). The magnitude of SD among men with DM varies across settings which ranges from 51%-85.5% (10,(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%